Power, Property Rights, and Economic Development The Case of Bangladesh - Miah, Mohammad Dulal (Springer Singapore, 2018)
This book presents a critical reassessment of theories of property rights, in response to conflicts and competition between different groups, and the state. It does so by taking an institutional political perspective to analyse the structures of property rights, with a focus on a series of case studies from Bangladesh. In doing so, the book highlights the importance of property rights for economic growth, why developing countries often fail to design property rights conducive for economic development, and the strategies required for designing an efficient structure of rights. Since property rights falls within the domain of Law and Economics, the book ventures to explain legal issues from an economic perspective, resulting in empirical analysis that comprises both legal and non-legal cases. Mohammad Dulal Miah received his PhD in Development Economics from Ritsumeikan Asia Pacific University, Japan. His research interests include property rights, economic development, the economics of rents and justice seeking, comparative financial system, corporate governance, etc. Yasushi Suzuki is a Professor at the College of International Management, Ritsumeikan Asia Pacific University, Japan. His primary research interest focuses on the institutional political economy of financial development.